Effects of Biostimulant and Zinc (Zn) Treatment on Qualitative and Quantitative Indicators of Winter Rape (Brassica Napus L.) - Lajos Kubina; Zoltán Molnár; Bálint Süle; Zsolt Giczi; Viktor Nagy; Renátó Kalocsai (Chemical Engineering Transactions)
Winter rapeseed production has completely changed in Hungary in recent years. The use of hybrids has become commonplace, and intensive cultivation techniques are widespread. At the same time, average yields also increased, making rapeseed one of the most profitable crops. Maintaining profitability is a priority task, and in addition to further increasing average yields, improving quality parameters and crop safety is also decisive. Rapeseed production today faces significant challenges. As a result of climate change, the cultivation routine of decades is changing, and biostimulators are becoming more and more perspective in addition to foliar fertilisation with macro- and microelements. During this research, a 3-year small-plot field experiment was set up with a winter rapeseed indicator. The main objective of the experiment was to study the physiological reactions of rape plants to different doses of Zn and the combined reaction of the biostimulator and Zn. During the experiment, the reaction of the rapeseed test plant on zinc-deficient calcareous chernozem soils was investigated under the influence of different doses of Zn and combined doses of Zn and biostimulation. The aim of the study is to determine whether rapeseed plants respond to zinc supplementation and the combined effect of the bio stimulator and zinc with increased yield and improved nutritional values (protein content, oil content). In the first annual study, two treatments were performed, one in autumn (BBCH 16-18 phenological stage) and one in spring (BBCH 29 phenological stage). Zinc tetramine hydroxide was used in 4 different doses (2, 5, 10, 20 L/ha), zinc tetramine hydroxide enriched with copper in 2 different doses (5 and 10 L/ha), Quantis in the manufacturer's prescribed dose of 2 L/ha, biostimulant enriched with zinc, and a usual foliar fertiliser used in rapeseed growing with Wuxal boron at the dose recommended by the manufacturer. During the growing season, the development of root mass, root length, SPAD values, as well as the yield and oleic acid content were evaluated by mathematical statistical method. It can be stated that there was no significant difference in the root mass, root length, and SPAD values, but there was a significant yield difference in the amount of the crop in the second-year experiment (P = 10 %). Studies have shown that biostimulants have the greatest influence on the development of measured parameters.